2016
DOI: 10.4236/acs.2016.61011
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Ozone Layer Depletion and Its Effects on Human: Review

Abstract: This study was conducted at University of Gujrat during 2014-2015 as a term paper for Master of Philosophy. The data regarding effect of ozone depletion on human was reviewed and compiled as a review paper from various published articles of international reputed journals, annual/environmental reports of recognized organization and e-books. The causes, mechanism and bio-effects of ozone layer depletion on humans were addressed. It is revealed that introduction of Chloroflourocarbons (CFCs) in the environment is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…It is estimated that one out of five Americans will develop skin cancer in their lifetime [2] . As Earth's protective ozone layer becomes thinner [3] the prevention of exposure to dangerous UV-intensities is of crucial interest [4] . Data on instantaneous and cumulative UV exposures provide important information for dermatology, skin and general healthcare and eventually help to prevent damages to the dermis, epidermis [5] or eyes [6] .…”
mentioning
confidence: 99%
“…It is estimated that one out of five Americans will develop skin cancer in their lifetime [2] . As Earth's protective ozone layer becomes thinner [3] the prevention of exposure to dangerous UV-intensities is of crucial interest [4] . Data on instantaneous and cumulative UV exposures provide important information for dermatology, skin and general healthcare and eventually help to prevent damages to the dermis, epidermis [5] or eyes [6] .…”
mentioning
confidence: 99%
“…Freon, a halohydrocarbon, and N 2 O can produce the greenhouse effect and can also react with stratospheric ozone, resulting in the depletion of the ozone layer and creation of holes in the ozone layer [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decline of the stratospheric ozone level from anthropogenic source is internationally recognized as one of the Earth’s most important environmental issues [ 13 ]. The ozone hole is affecting human health and the environment negatively and can cause severe diseases, such as skin cancer, eye damage, and genetic mutations [ 10 , 12 ]. Research results show that if stratospheric ozone concentrations decreased by 1%, the amount of ultraviolet radiation will be increased by 2%, and the cataract rate will increase 0.2–0.6%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ozone layer is a region of the Earth's stratosphere that absorbs most of the Sun's ultraviolet (UV) radiation (Anwar et al, 2016). Historical measurements -pre-1980 -indicated that the morphology of the ozone was not changing significantly with time.…”
Section: Introductionmentioning
confidence: 99%